2002
DOI: 10.1086/340343
|View full text |Cite
|
Sign up to set email alerts
|

QSO 2237+0305VRLight Curves from Gravitational LensES International Time Project Optical Monitoring

Abstract: We present V R observations of QSO 2237+0305 conducted by the GLITP collaboration from 1999 October 1 to 2000 February 3. The observations were made with the 2.56 m Nordic Optical Telescope at Roque de los Muchachos Observatory, La Palma (Spain). The PSF fitting method and an adapted version of the ISIS subtraction method have been used to derive the V R light curves of the four components (A-D) of the quasar. The mean errors range in the intervals 0.01-0.04 mag (PSF fitting) and 0.01-0.02 mag (ISIS subtractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 11 publications
5
74
0
2
Order By: Relevance
“…Photometric monitoring revealed uncorrelated variability between the various images, interpreted as being due to gravitational microlensing (Irwin et al 1989). This interpretation was confirmed with dedicated monitoring programs (e.g., Østensen et al 1996;Woźniak et al 2000a,b;Alcalde et al 2002). Q2237+0305 is the best studied quasar microlensing system.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Photometric monitoring revealed uncorrelated variability between the various images, interpreted as being due to gravitational microlensing (Irwin et al 1989). This interpretation was confirmed with dedicated monitoring programs (e.g., Østensen et al 1996;Woźniak et al 2000a,b;Alcalde et al 2002). Q2237+0305 is the best studied quasar microlensing system.…”
Section: Introductionmentioning
confidence: 70%
“…to be compared with Alcalde et al 2002, for data reduction details and results). The R band photometry used here is shown in Fig.…”
Section: Monitoring Observations Of Q2237+0305mentioning
confidence: 99%
“…Soon after its discovery, photometric monitoring of the individual images revealed that they possessed uncorrelated variability; this was interpreted as being due to gravitational microlensing by compact objects in the lensing galaxy (Irwin et al 1989). This conclusion was confirmed with further monitoring of this system, revealing complex variability consistent with the quasar being swept with the high magnifications associated with caustics Østensen et al 1996;Vakulkik et al 1997;Woźniak et al 2000;Alcalde et al 2002;Schmidt et al 2002). Two recent campaigns have provided exquisite light curves for the four images in this system; OGLE (Woźniak et al 2000) consists of low temporal sampling over a long time frame, while GLITP ) was a short, targeted campaign, undertake at high temporal sampling.…”
Section: Introductionmentioning
confidence: 52%
“…This makes possible some estimations of certain GLS characteristics, in particular, the source size [25]. For example, in case of the well-known GLS Q2237+0305 (Einstein Cross), several HAEs was observed [26][27][28] and the estimates of the source size have been obtained within different source models [16,[29][30][31][32][33][34].…”
Section: Preliminary Commentsmentioning
confidence: 99%
“…On the other hand, a number of authors [4,16,[33][34][35][36][37][38][39] discussed delicate questions concerning determination a fine quasar structure from HAE. For example, the authors of [36] wrote that the GLITP data [28] on Q2237+0305 admit only accretion disc models (see also [4,39]). Obviously, the presence of an accretion disk in a central region of quasar is beyond any doubts, as well as the fact that the real appearance of the quasar core can be quite different from our simplified models.…”
Section: Preliminary Commentsmentioning
confidence: 99%